Challenges facing female muslim medical practitioners (FMMP) in the University College Hospital (UCH), Ibadan, Nigeria (2020)
In Nigeria, religious intolerance between Muslims and Christians continues to increase. Muslim women are among those who have felt the most impact from the resulting religious prejudice, intolerance, and discrimination, especially in their workplaces. While many studies have been conducted to investigate the myriads of challenges facing women in general and Muslim women in particular, little research has been done on the challenges they face in their workplaces. This study intends to fill this gap by studying Female Muslim Medical Practitioners (FMMP) at the University College Hospital (UCH), Ibadan, Nigeria. Purposive and snowball samplings were used to select seventy research participants. Face-to-face and in-depth individual interviews, which lasted between 30 minutes and three hours each, were used to collect data for the study, in which relevant statistical tests were used for data analysis. The study reveals that FMMPs in the hospital encounter several challenges, such as donning the hijab (the Muslim headscarf), performing daily prayers (salat), and employment opportunities. There is also evidence of high-level discrimination in the workplace. Finally, the study recommends that the management of UCH enhance its practice and policies regarding religious tolerance, equality, fairness, unity, and cooperation amongst its administrative staff and personnel.